Botulinum toxin for the treatment of dystonia and pain in corticobasal syndrome. Issue 6 (9th May 2019) - Unti, Elisa; Mazzucchi, Sonia; Calabrese, Rosanna; Palermo, Giovanni; Del Prete, Eleonora; Bonuccelli, Ubaldo; Ceravolo, Roberto
Abstract: Background: Dystonia is a key symptom in corticobasal syndrome (CBS), and upper limb dystonia is the most common phenotype. Dystonia‐associated pain is frequently reported and can be disabling, with poor benefit from oral treatments. Aims of the Study: To investigate the role of botulinum toxin A (BoTNA) in the treatment of dystonia and associated pain in CBS. Methods: Ten consecutive patients with a clinical diagnosis of probable CBS and dystonia with/without associated pain were treated with BoTNA every 3 months. Treatment efficacy was assessed during the first follow‐up visit, three months after the first injection, by means of caregiver impression (CI), evaluation of muscle tone with the Ashworth scale (AS), severity of pain measured with the visual analog scale (VAS). Results: Nine subjects underwent at least three treatments, four patients discontinued for progressive reduction in efficacy or disease progression, five patients are ongoing with good response, and one completed the 10th treatment. No local or systemic side effects were reported, and levodopa equivalent daily dose remained unchanged in most cases during the observational period. Significant improvement of AS was recorded (from 2.9 ± 0.7 to 2.0 ± 0.5, p = 0.003). CI ranged from mild to moderate benefit. All patients reported efficacy on pain, with a significant reduction of VAS score (from 7.7 ± 1.7 to 1.7 ± 0.7 in the Pain group, p = 0.016). Conclusions: Our study confirms safety, efficacy, and tolerability of BoTNA in the treatment of dystonia associated with CBS. Local treatment should be considered as a valid alternative to oral treatment modulation mainly in the presence of associated pain. Abstract : Dystonia is a key symptom in corticobasal syndrome (CBS), and upper limb dystonia is the most common phenotype. The role of botulinum toxin A (BoTNA) in the treatment of dystonia and associated pain in CBS has been not investigated so far Our study confirms safety, efficacy, and tolerability of BoTNA in the treatment of dystonia associated to CBS and related pain in 10 subjects.